Pleiotropic roles of the insulin-like growth factor axis in type 1 diabetes. Issue 4 (August 2019) - Shapiro, Melanie R.; Atkinson, Mark A.; Brusko, Todd M.
Abstract : Purpose of review: We review studies demonstrating lowered levels of insulin-like growth factors (IGFs) in patients with recent-onset type 1 diabetes (T1D) and discuss their potential roles in the disorder's pathogenesis. Recent findings: IGFs have long been recognized as a class of hormones that promote growth, development, and cellular metabolism throughout the human body. More recently, studies have noted an association between reduced pancreatic weight/volume and T1D. Thus, we believe it is important to understand pancreatic regulation of IGF expression and bioavailability, as well as the impact of IGFs on pancreatic growth and islet health. Additional studies of IGFs have been extended to their influence on the inflammatory/regulatory balance of monocytes, B cells, and T cells; features which have been previously established to show dysregulation in settings of T1D. Summary: These data suggest that IGFs may prevent known impairments in the pancreas and immune system in T1D and underscore the need to extend these studies, some of which were performed in health or other autoimmune diseases, toward T1D specifically. Collectively, the work emphasized here support the potential therapeutic use of IGFs in T1D prevention efforts as pancreatic growth factors and/or immunoregulatory agents.